The Effect of Numbered Head Together Learning Model on Social Skills and Learning Outcomes of IPS Class V Students - Beatrisda Effi Guniarti; Jamaluddin Arifin; Idawati Idawati (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the Numbereed Head Together Learning Model for social skills and social studies learning outcomes for Cluster II Students in Ujung Tanah District. This type of research is quantitative research. This research uses a quasi-experimental research type. The subjects used in this study were students in class V cluster II, Ujung Tanah District, Makassar City with a total of 60 students. The instruments used in this study were data collection instruments, namely tests, observations and documentation sheets. Descriptive and inferential test analysis techniques (manova). Based on the results of the t-test analysis, the application of the Numbered Head Together learning model to social skills and social studies learning outcomes in cluster II, Ujung Tanah District, Makassar City has increased significantly. The results of the manova test of Numbered Head Together Learning on social skills and social studies learning outcomes in cluster II, Ujung Tanah District, Makassar City show a significant increase, so